2014
DOI: 10.1159/000369613
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Force-Induced Specific MicroRNA Expression in Human Periodontal Ligament Stem Cells

Abstract: It remains unclear how the expression of microRNAs (miRNAs) in human periodontal ligament stem cells (PDLSCs) might respond to mechanical stretch. To investigate specific miRNA expression in stretched PDLSCs, we used a Flexcell® FX-5000™ tension system to achieve external mechanical stimulation. Then, a custom-designed microarray assay was performed to investigate and describe the genome-wide differential expression of miRNAs in normal and stretched PDLSCs. Finally, we implemented integrative miRNA target pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 35 publications
(32 reference statements)
0
54
0
1
Order By: Relevance
“…Several miRNAs have been reported for their expression and roles in PDL and alveolar bones [115][116][117][118]. Under loading, several miRNAs in PDL and alveolar bone respond to the loading force and orientation of forces in different pattern of expression [119][120][121]. miRNA-21 has been shown to have critical roles in PDL, osteoblasts and osteoclasts [120,[122][123][124][125][126][127].…”
Section: Future Of Genetic Manipulation Of Tooth Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…Several miRNAs have been reported for their expression and roles in PDL and alveolar bones [115][116][117][118]. Under loading, several miRNAs in PDL and alveolar bone respond to the loading force and orientation of forces in different pattern of expression [119][120][121]. miRNA-21 has been shown to have critical roles in PDL, osteoblasts and osteoclasts [120,[122][123][124][125][126][127].…”
Section: Future Of Genetic Manipulation Of Tooth Movementmentioning
confidence: 99%
“…Under loading, several miRNAs in PDL and alveolar bone respond to the loading force and orientation of forces in different pattern of expression [119][120][121]. miRNA-21 has been shown to have critical roles in PDL, osteoblasts and osteoclasts [120,[122][123][124][125][126][127]. In addition, miRNA-21 deficient mouse demonstrated delayed tooth movement compared to the control mice via inhibition of osteoclastogenesis [127].…”
Section: Future Of Genetic Manipulation Of Tooth Movementmentioning
confidence: 99%
“…miRNAs bind to the specific mRNA recognition sequences that are located in the 3′ untranslated regions (3′ UTRs) of the target mRNA, which leads to mRNA degradation or protein translation interference [18]. Recent studies have demonstrated that miRNAs are differentially expressed between cyclically-stretched and non-stretched periodontal ligament stem cells (PDLSCs) [18,19,20], and the pattern is closely related to the mRNA expression of osteogenic markers, which indicates the important regulatory roles of miRNA in bone remodeling of orthodontic tooth movements. However, hitherto, the miRNA expression pattern of mature cementoblasts has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, circRNAs have been proved to act as potent miRNAs sponges to regulate relevant genes (Hansen et al, 2013). Interestingly, previous studies revealed that 53 specific miRNAs were differentially expressed with MF, which implied that miRNAs may play a crucial part in the osteogenic differentiation of PDLSCs (F. L. Wei et al, 2014). They also found that the time-dependent increased miR-21 with MF could mediate the stretch-induced osteogenic differentiation of PDLSCs (F. Wei, et al, 2015).…”
mentioning
confidence: 99%